Pemahaman Keagamaan Guru dan Sikap Beragama Anak Usia Dini di TKIT Al-Washliyah Hamparan Perak Deli Serdang - Rahman, Mhd Habibu; Lubis, Sofni Indah Arifa; Audy, Rini Trinasya; Anggraini, Lita (AS-SABIQUN, 2023)
The development of religious attitudes in early childhood is almost completely authoritative, which means that it will develop under the influence of factors from outside the child. One of the factors that influence the religious attitude of early childhood is the religious understanding possessed by the teacher. The purpose of this study was to find out the teacher's religious understanding and religious attitudes of children in IT Al-Washliyah Kindergarten, and to find out what obstacles were found in building children's attitude of religious inclusiveness in IT Al-Washliyah Kindergarten, Hamaparan Perak District, Deli Serdang Regency. The method used in this research is qualitative with data collection techniques carried out participant observation, in-depth interviews. All existing data were analyzed by means of data condensation, data display and verification stages. The findings in this study are that the teacher's religious understanding determines the religious attitude of children. The teacher's religious understanding at TK IT Al-Washliyah prioritizes humanist values and inclusiveness, children are given freedom of thought, carry out activities carried out by children in religious activities by respecting differences in the way friends worship, helping friends who are in trouble, being friendly to friends who have different understandings with him. The inclusive attitude that children have in religion is an explanation of children's openness to tolerance, being able to accept and interact with friends who have different understandings and cultures than children.